2018
DOI: 10.1016/j.epsl.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

“Virtual shear box” experiments of stress and slip cycling within a subduction interface mélange

Abstract: What role does the progressive geometric evolution of subduction-related mélange shear zones play in the development of strain transients? We use a "virtual shear box" experiment, based on outcrop-scale observations from an ancient exhumed subduction interface-the Chrystalls Beach Complex (CBC), New Zealand-to constrain numerical models of slip processes within a meters-thick shear zone. The CBC is dominated by large, competent clasts surrounded by interconnected weak matrix. Under constant slip boundary condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…SSEs can be represented by slow stick-slip instabilities caused by competing weakening and strengthening rate-and-state mechanisms (Rubin, 2008), variation in pore pressure (Bernaudin & Gueydan, 2018), or alternating clast-supported and matrix-supported bulk rheology (Lavier et al, 2013;Webber et al, 2018). Our mélange models undergoing progressive jamming demonstrate that the most generalized mélange can switch between matrix support and clast support, resulting in significant η eff variation through time.…”
Section: Stick-slip Creep Behavior and Slow Slip Eventsmentioning
confidence: 91%
See 1 more Smart Citation
“…SSEs can be represented by slow stick-slip instabilities caused by competing weakening and strengthening rate-and-state mechanisms (Rubin, 2008), variation in pore pressure (Bernaudin & Gueydan, 2018), or alternating clast-supported and matrix-supported bulk rheology (Lavier et al, 2013;Webber et al, 2018). Our mélange models undergoing progressive jamming demonstrate that the most generalized mélange can switch between matrix support and clast support, resulting in significant η eff variation through time.…”
Section: Stick-slip Creep Behavior and Slow Slip Eventsmentioning
confidence: 91%
“…Above a critical ϕ, deformation may be accommodated by brittle faulting of strong blocks and localized strain of the intervening matrix (Fagereng & Sibson, 2010). Such localized slip can occur transiently when matrix shear pathways are blocked by interlocking clasts (e.g., Webber et al, 2018), so that a subset of clasts become load-bearing force chains in a process called 'jamming' (Cates et al, 1998). It is unclear what this critical ϕ is; estimates vary from ϕ ≈ 0.45 (Roscoe, 1952) to ≥0.8 (Handy, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several field (Fagereng & Sibson, ; Handy, ) and numerical (Jammes et al, ; Webber et al, ) studies have indicated that the brittle to viscous phase ratio controls the type of deformation. This can lead to three different deformation styles: (1) The strong, brittle phase provides a stress supporting framework leading to dominantly brittle deformation, (2) rheology is controlled by the flow of the weak, ductile phase where stronger asperities are isolated, and (3) where both phases accommodate strain by a mixture of localized brittle failure and ductile flow (Figure ).…”
Section: Implications For Natural Systemsmentioning
confidence: 99%
“…The overall idea is that an abundant viscous fluid phase would lead to a creep signal, whereas an abundant brittle phase would lead to a stick‐slip signal. The impact of a semibrittle rheology on the transition between creep and stick‐slip has been investigated in a number of physical experiments (Burton et al, ; Moore, ; Reber et al, ) as well as theoretical (Lavier et al, ) and numerical (Jammes et al, ; Webber et al, ) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Where pods are in direct contact with each another, brittle fracture networks radiate outwards from the contact zone ( Fig. 12b-iii), suggesting that local stresses in the pods were transiently elevated as they were brought in to contact (Webber et al, 2018).…”
Section: A Model For the Internal Structure And Composition Of Plate mentioning
confidence: 99%